Significance of catestatin in the pathogenesis of heart failure with preserved ejection fraction in patients with non-obstructive coronary artery disease - E. V. Grakova; K. V. Kopieva; A. M. Gusakova; A. V. Smorgon; A. N. Maltseva; A. V. Mochula; A. V. Svarovskaya; K. V. Zavadovsky (Российский кардиологический журнал)
Aim. In patients with non-obstructive coronary artery disease (CAD), to evaluate the pathophysiological significance and diagnostic effectiveness of catestatin in detecting heart failure with preserved ejection fraction (HFpEF), as well as to assess the relationship of the levels of this biomarker with heart rate variability (HRV) parameters and the severity of diastolic dysfunction.Material and methods. The study included 83 patients (44 men, mean age, 62,0 [57,0; 68,5] years) with non-obstructive CAD and preserved left ventricular (LV) ejection fraction of 63 [60; 64]%). Echocardiography was performed according to a standard protocol. HRV was assessed using 24-hour electrocardiographic monitoring. Serum biomarker levels were determined using enzyme-linked immunosorbent assay.Results. Patients were divided into groups depending on HFpEF presence: group 1 (n=63) included patients with newly diagnosed HFpEF, and group 2 included patients without heart failure (n=20). Serum catestatin concentrations were 43,1% lower (p<0,001) in patients with HFpEF than in patients without it. Catestatin had a negative correlation with levels of N-terminal pro-brain natriuretic peptide and C-reactive protein. Moreover, serum catestatin values were inversely correlated with LV remodeling parameters, whereas no relationship was found with HRV values. According to ROC analysis, catestatin £132,83 μg/ml (AUC=0,884; p<0,001) were defined as threshold values associated with HFpEF.Conclusion. Decreased serum catestatin concentrations were associated with HFpEF and overexpression of heart failure and inflammation biomarkers. Moreover, serum catestatin values had a negative relationship with LV remodeling parameters, while no relationship was found with HRV values.